Causes of death in Japanese patients with diabetes based on the results of a survey of 68,555 cases during 2011–2020: Committee report on causes of death in diabetes mellitus, Japan Diabetes Society (English version) - Jiro Nakamura; Narihito Yoshioka; Hideki Katagiri; Kohjiro Ueki; Toshimasa Yamauchi; Nobuya Inagaki; Yukio Tanizawa; Eiichi Araki; Takeo Nakayama; Hideki Kamiya (Journal of Diabetes Investigation)
ABSTRACT The principal causes of death among 68,555 patients with diabetes and 164,621 patients without diabetes who died in 208 hospitals throughout Japan between 2011 and 2020 were determined based on a survey of hospital records. The most frequent cause of death in patients with diabetes was malignant neoplasms (38.9%) (lung 7.8%, pancreas 6.5%, liver 4.1%), followed, in order of descending frequency, by infectious diseases (17.0%) and then vascular diseases (10.9%) (cerebrovascular diseases 5.2%, ischemic heart diseases 3.5%, renal failure 2.3%). The proportion of deaths from malignant neoplasms and vascular diseases has trended upward and downward, respectively. Almost all deaths from ischemic heart diseases were due to myocardial infarction, and the proportion of deaths from heart diseases other than ischemic heart diseases was relatively high (9.0%), with most cases due to heart failure. Diabetic coma associated with hyperglycemia accounted for only 0.3% of deaths. The proportion of deaths from malignant neoplasms, infectious diseases, renal failure, ischemic heart diseases, and heart failure was significantly higher in patients with diabetes than in those without diabetes, and the proportion of deaths from cerebrovascular diseases was significantly lower in patients with diabetes. With regard to the relationship between the age and cause of death in patients with diabetes, malignant neoplasms were the most frequent cause of death in all age groups, and the incidence was around 50% for those in their 50s and 60s. The incidence of death due to infectious diseases was highest in patients older than their 70s. The incidence of death due to vascular diseases for patients in their 40s and 50s was higher than that due to infectious diseases. The highest incidence of death due to ischemic heart diseases was observed for patients in their 40s, and that due to renal failure and heart failure in patients older than their 70s. Compared with patients without diabetes, patients with diabetes demonstrated a higher incidence of death due to pancreatic cancer, infectious diseases, renal failure, ischemic heart diseases, and heart failure, and a lower incidence of death due to cerebrovascular diseases in all age groups. The average age at death of patients with diabetes was 74.4 years old in men and 77.4 years old in women, which were lower than the average lifespan of the Japanese general population in 2020 by 7.2 and 10.3 years, respectively. However, these differences were smaller than in previous surveys. The average age at death due to all causes, especially due to ischemic heart diseases, cerebrovascular diseases, heart failure, infectious diseases, and diabetic coma, was lower in patients with ‘poorer’ glycemic control than in those with ‘better’ glycemic control. In the total survey population, the average age at death of patients with diabetes was significantly higher than that of patients without diabetes. The average age at death due to malignant neoplasms and cerebrovascular diseases was higher in patients with diabetes than in those without diabetes and that due to renal failure, ischemic heart diseases, and infectious diseases was lower in patients with diabetes than in those without diabetes.